Acetic Acid Catalysed One-Pot Synthesis of Pyrrolo[1,2-a]quinoxaline Derivatives - Allan, Pia N. M.; Ostrowska, Martyna I.; Patel, Bhaven (Synlett, 2019)
An efficient acetic acid catalysed reaction has been developed for the synthesis of 4-aryl substituted pyrrolo[1,2-a]quinoxalines from readily available starting materials. A range of structures have been synthesised in very good to excellent yields. The one-pot reaction proceeds through imine formation, cyclisation followed by air oxidation.
Keywords: pyrrolo[1,2-a]quinoxaline; catalysis; Pictet–Spengler reaction; 1-(2-aminophenyl)pyrroles; biological heterocycles